Analysis of Hospital Based Urine Drug Screening Tests over 2 Years. Does it Mirror the Actual Prevalence of Drug Abuse! - Bhutada, T; Ray , A; Behera, B K; Dash , B K; Otta, S (Journal of Indian Academy of Forensic Medicine, 2023)
Effect of drugs often interplays with the diagnosis and treatment of patients presenting to Emergency and critical care services of the hospital. Urine drug screen (UDS) is a qualitative toxicological screening tool which is simple, fast and has a relatively low cost providing a clue in acute care settings. The present study aims to determine the prevalence of drugs of abuse determined by UDS in suspected patients in a hospital set up and compare it to national prevalence study. It is a retrospective study conducted in the Toxicology lab in KIMS Medical College and Hospital, in Odisha over a period of 30 months where urine samples received from the hospital were included. Commonly abused substances were detected by urine drug screen by the help of a commercially available lateral flow assay kit. We received 232 samples in this study period of which 108 (46.5%) tested positive by urine drug screen.The highest positivity among the samples was noted in the age group of 21-30 (33.3%) closely followed by 11-20 (30.6%) with a male preponderance.(32.3%) cases where single drug was found in urine drug screen while 33 (14.2%) of cases had multiple drugs detected in the UDS. Most common substance of abuse was benzodiazepines in 43.2% cases. THC (29.05%) and OPI (14.2%) were the other commonly abused drugs. In poly drug abusers, commonest drug combination consisted of OPI and THC with or without BZO in 36.36 % (12 /33) cases. Thus, in spite of having many limitation of urine drug screen will help in the acute patient care set up particularly for diagnosis of poly drug abuse.